1980
DOI: 10.1259/0007-1285-53-629-432
|View full text |Cite
|
Sign up to set email alerts
|

Renal lesion in Jeune's syndrome

Abstract: In three children, presenting in chronic renal failure at the ages of six, four and three years radiology suggsested the diagnosis of Jeune's syndrome (asphyxiating thoracic dysplasia). In each case the skeletal survey showed widespread diagnostic features of this condition. The syndrome is characterized by varying degrees of repiratory distress in infancy and early childhood, with osseous dl three children in this study died from juvenile nephronopthisis. The correct diagnosis is essential for patient managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

1985
1985
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 10 publications
2
16
0
2
Order By: Relevance
“…Similar renal anomalies are described in patients with ATD [5,6]. Chronic renal failure secondary to nephronophthisis is described in older children with ATD [7].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Similar renal anomalies are described in patients with ATD [5,6]. Chronic renal failure secondary to nephronophthisis is described in older children with ATD [7].…”
Section: Discussionsupporting
confidence: 54%
“…Pulmonary insufficiency is severe and more frequent, whereas dental and cardiac defects are less common in patients with ATD than in patients with EvC syndrome. Reported renal anomalies in ATD include agenesis, dysplasia, and congenital megaureter [5,6]. While nephronophthisis has been occasionally reported in older children with ATD [6,7], it has, however, not been described in patients with EvC syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it is present, the postaxial polydactyly occurs most frequently in the distribution of bilateral hands and feet. The frequency of hepatic problems occurs in <30% of reported cases, and it is difficult to predict risk of developing liver disease based upon the presence of skeletal findings [Karjoo et al, 1973;Friedman et al, 1975;Oberklaid et al, 1977;Shah, 1980;Turkel et al, 1985;Hudgins et al, 1990;Labrune et al, 1999;Krakow et al, 2000;Kajantie et al, 2001;Ö zçay et al, 2001;Morgan et al, 2003;Yerian et al, 2003;Tuysuz et al, 2009;De Vries et al, 2010;Lehman et al, 2010]. In addition, from review of the literature, most cases with hepatic structural changes are identified at autopsy, but are usually clinically mild, stable, or resolve with therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Renal findings of hypertension in 2nd-3rd year of life, renal cysts (which may progress to tubular atrophy), and renal failure occurring in infancy, adolescence, or second decade of life are reported [Oberklaid et al, 1977], none of which were found in these eight cases. Renal failure occurred in 38% of those with kidney involvement [Oberklaid et al, 1977;Shah, 1980;Ring et al, 1990;Amirou et al, 1998;Tuysuz et al, 2009;De Vries et al, 2010]. The predominant cause of death for patients aged 3-10 years is renal in origin.…”
Section: Discussionmentioning
confidence: 99%